An ambipolar PEDOT-perfluorinated porphyrin electropolymer: Application as an active material in energy storage systems - Bermúdez Prieto, Elizabeth (2024)
The development of functional organic materials is crucial for the advancement of various fields, such as optoelectronics, energy storage, sensing, and biomedicine. In this context, we successfully prepared a stable ambipolar perfluoroporphyrin-based polymeric film by electrochemical synthesis. Our strategy involved the synthesis of a novel tetra-pentafluorophenyl porphyrin covalently linked to four 3,4- ethylenedioxythiophene (EDOT) moieties. The resulting monomer, EDOT-TPPF16, was obtained through a straightforward synthetic approach with a good overall yield. The unique molecular structure of EDOTTPPF16 serves a dual function, with EDOT moieties allowing electropolymerization for polymeric film formation, while the electron-acceptor porphyrin core enables electrochemical reduction and electron transport. The electrochemical polymerization permits the polymer (PEDOT-TPPF16) synthesis and film formation in a reproducible and controllable manner in one step at room temperature. Spectroelectrochemical experiments confirmed that the porphyrin retained its optoelectronic properties within the polymeric matrix after the electrochemical polymerization. The obtained polymeric material exhibited stable redox capabilities. Current charge–discharge cycles and electrochemical impedance spectroscopy of the electrochemically generated organic film demonstrated that the polymer could be applied as a promising active material in the development of supercapacitor energy storage devices.